Measuring the Effect of Internet Adoption on Paper Consumption - Andres, Luis (World Bank Group, Washington, DC, 2014)
A large fraction of the total supply of paper is produced with technologies that have serious adverse consequences on the environment and cause significant health problems, such as cancer. This paper reports on how Internet adoption affects paper consumption. The study used country-level panel data on Internet penetration and paper consumption disaggregated into various paper categories. The empirical strategy is to use fixed-effect models to study whether countries with faster Internet penetration growth have experienced faster declines in paper consumption. The analysis finds that Internet penetration significantly decreases aggregate paper consumption. Further, the estimates show that Internet growth reduces consumption for the paper categories that are more likely to be affected by the diffusion of the Internet (paper used to print newspapers and books and magazines), whereas the growth of the Internet does not have a statistically significant impact on a paper category unlikely to be affected by the Internet (such as sanitary paper).